Oxidized glutathione and its crystalline form and method for preparing impurities
The synthesis of oxidized glutathione heptahydrate using DMSO and controlled crystallization in purified water addresses the challenges of existing methods, achieving high purity and stability, suitable for industrial production.
Patent Information
- Application Number
- JP2024538126
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-08
- Filing Date
- 2022-12-20
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-12-20
AI Technical Summary
Current methods for synthesizing oxidized glutathione face challenges such as harsh reaction conditions, low product purity, high cost, and difficulty in achieving large-scale industrial production, along with issues in crystal form stability and impurity removal.
A method involving the use of dimethyl sulfoxide (DMSO) as an oxidizing agent and controlled crystallization in purified water with iron(II) chloride to produce oxidized glutathione heptahydrate crystals, characterized by specific X-ray diffraction peaks and thermogravimetric analysis, achieving high purity and stability.
The method provides oxidized glutathione with high purity (>99.9%) and low impurity content, suitable for industrial production, and introduces a new crystalline form with improved water solubility and stability, simplifying purification processes.
Smart Images

Figure 2025501596000026 
Figure 2025501596000027 
Figure 2025501596000028
Abstract
Description
[Technical field]
[0001] The present disclosure is in the field of chemical synthesis, and in particular relates to methods for preparing oxidized glutathione and its heptahydrate crystalline form, as well as impurities. [Background technology]
[0002] Oxidized glutathione has similar effects as reduced glutathione, but it is more stable than reduced glutathione and therefore can be used instead of reduced glutathione as an active ingredient in health foods, medicines, cosmetics, and other products.
[0003] All currently reported methods for preparing oxidized glutathione are based on the oxidation of reduced glutathione, for example:
[0004] Route 1: Oxidation by hydrogen peroxide (Chinese Journal of Pharmaceuticals, 2013, 44, 265). The method includes the following steps: dissolving reduced glutathione in water, adjusting the resulting solution to a suitable pH value, and oxidizing glutathione with hydrogen peroxide as an oxidizing agent to prepare oxidized glutathione. The disadvantage of this method is that the rate of hydrogen peroxide oxidation reaction is relatively fast, but the reaction is also relatively violent, so the reaction conditions are relatively harsh and the process parameters such as temperature, pH and the amount of hydrogen peroxide in the reaction system need to be strictly controlled. In other respects, further peroxidation or decomposition impurities will be generated, affecting the purity and yield of the product. In addition, the oxidizing agent, hydrogen peroxide, is a hazardous compound in China that can easily make explosives, and therefore the use of hydrogen peroxide is regulated. In addition, hydrogen peroxide is prone to self-decomposition and needs to be stored in a closed container at low temperature.
[0005] Route 2: Catalysis by Arginine (RSC Adv., 2014, 4, 33399-33407). The method includes the following steps: dissolving reduced glutathione in water, and using oxygen gas as an oxidant and arginine as a catalyst. The reaction does not produce waste, which is green and environmentally friendly. In addition, oxygen gas and arginine are relatively easy to obtain, so the raw materials are relatively easy to obtain. The disadvantages of this method are: since arginine needs to be used as a catalyst in the reaction process, residual arginine is likely to remain during the work-up process, and since the reaction needs to be heated to 50°C, the product, i.e., oxidized glutathione, is prone to partial decomposition and racemization under high temperature conditions, resulting in a low yield and low purity.
[0006] Route 3: Enzyme catalysis (JP Patent Publication No. 5-146279). This method is a bioenzyme catalysis method, which requires the use of a specific biooxidase as a catalyst and uses air to oxidize reduced glutathione aqueous solution to obtain oxidized glutathione. The disadvantages of this method are: the enzyme is relatively difficult to obtain and store, and is not as good as commonly used chemical reagents. In addition, after the reaction is completed, the enzyme needs to be separated from the reaction solution, which requires specific process technology and equipment. It may not be applicable to the existing equipment of ordinary chemical raw materials pharmaceutical companies.
[0007] Route 4: Diethyl bromomalonate method (Chem. Pharm. Bull. 1986, 34, 486-495). The method includes the following steps: dissolving reduced glutathione in an alkaline water / ethanol solution, then adding an ethanol solution of diethyl bromomalonate dropwise, and reacting at -16°C for 1 hour. The disadvantages of this method are: the oxidizing agent is diethyl bromomalonate, which is relatively expensive, diethyl bromomalonate produces more by-products, and the operation is complicated. The reaction process requires a low temperature of -16°C, which is relatively unsuitable for industrialization.
[0008] In addition, the crystal forms of oxidized glutathione prepared by the above method mainly include non-crystalline amorphous form (CN102858792A), monohydrate crystal form (Japanese Patent No. 4401775), hexahydrate crystal form (CN102869674A) and octahydrate crystal form (International Union of Crystallography, pp538, 1999). Among these forms, the non-crystalline amorphous form has low water solubility, which limits its application in the pharmaceutical industry; the monohydrate crystal form is prone to agglomeration with needle-like crystals, and the impurities in the crystal form are difficult to remove, so the crystal separation ability is low; during the crystallization process of the hexahydrate crystal form, the pH needs to be adjusted, and the crystallization time is longer than 10 hours, so the operation is relatively troublesome and it is difficult to obtain crystals; and the octahydrate crystal form has uneven water content, low stability, and requires a long time of up to 3 to 4 days to obtain crystals. Furthermore, existing processes for oxidized glutathione have never achieved large-scale industrial production. The main reason is that it is difficult to simultaneously achieve reaction mildness (reducing product decomposition and racemization) and economy. To achieve good process stability, oxidation and crystallization systems are required that are mild, economical, easily available, and have few by-products.
[0009] Furthermore, detection by liquid chromatography and structural confirmation by mass spectrometry revealed that oxidized glutathione contains the following three impurities: [Table 1]
[0010] There are few reports on the preparation methods of these three impurities, and the raw materials and reagents used are not commercially available, therefore these preparation methods are of no practical value.
[0011] There are no literature reports on the purification process of oxidized glutathione. Because polypeptide compounds are easily hydrolyzed, racemized, and biodegraded, the commonly used purification method is separation by ion exchange resin chromatography or preparative liquid chromatography. The above methods have high solvent loss and high production costs.
[0012] In summary, there is a need in the art for a method for synthesizing oxidized glutathione that has low cost, mild reaction conditions, high product purity, and is suitable for industrial production. Summary of the Invention
[0013] Compared with existing methods, the method for synthesizing oxidized glutathione provided by the present disclosure can solve the above problems.
[0014] Specifically, the present disclosure relates to the following embodiments:
[0015] 1. Formula (I): [ka] A crystal of the heptahydrate of the compound.
[0016] 2. A crystal as described in embodiment 1, characterized by an X-ray powder diffraction pattern obtained using CuKα radiation having at least the following characteristic peaks in degrees 2θ: 8.238±0.2, 16.338±0.2, and 24.551±0.2.
[0017] 3. A crystal as described in embodiment 2, characterized by an X-ray powder diffraction pattern obtained using CuKα radiation having at least the following characteristic peaks in degrees 2θ: 10.619±0.2, 19.539±0.2, 26.806±0.2, and 34.618±0.2.
[0018] 4. A crystal as described in embodiment 3, characterized by an X-ray powder diffraction pattern obtained using CuKα radiation having at least the following characteristic peaks at °2θ: 9.750±0.2, 22.738±0.2, and 23.200±0.2.
[0019] 5. The crystal of embodiment 1, characterized by an X-ray powder diffraction pattern substantially as shown in FIG. 5.
[0020] 6. The crystal of any one of embodiments 1 to 5, further characterized by having a melting point of 169±2° C.
[0021] 7. The crystal according to any one of embodiments 1 to 6, further characterized by a weight loss of about 14±1% at 50 to 100° C. and a weight loss of about 3±1% at 100 to 160° C. in thermogravimetric analysis.
[0022] 8. The crystal of any one of the preceding embodiments, further characterized in that it has a thermogravimetric analysis diagram as shown in FIG.
[0023] 9.Formula (II) [ka] with DMSO to obtain a compound of formula (I), A process for preparing a compound of formula (I).
[0024] 10. The method of embodiment 9, wherein the molar ratio of DMSO to the compound of formula (II) is from 2:1 to 25:1, alternatively from 2.5:1 to 5:1, further alternatively 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1.
[0025] 11. The method of embodiment 9 or 10, wherein a polar solvent is further added to the reaction to facilitate dissolution of the compound of formula (II), or the polar solvent is selected from the group consisting of water, formamide, trifluoroacetic acid, acetonitrile, DMF, hexamethylphosphoramide, methanol, ethanol, acetic acid, isopropanol, pyridine, tetramethylethylenediamine, acetone, triethylamine, n-butanol, dioxane, tetrahydrofuran, methyl formate, tributylamine, methyl ethyl ketone, ethyl acetate, chloroform, trioctylamine, dimethyl carbonate, and diethyl ether, or combinations thereof, and alternatively water.
[0026] 12. The method of embodiment 11, wherein the ratio of polar solvent to compound of formula (II) is 200 to 2000 mL, alternatively 250 mL to 1000 mL, further alternatively 250 mL, 300 mL, 500 mL, 750 mL or 1000 mL of polar solvent per 100 g of compound of formula (II).
[0027] 13. The method of any one of embodiments 9 to 12, wherein the pH of the reaction is adjusted to between 2 and 9, alternatively between 3 and 7, further alternatively between 5 and 7, such as 5, 5.5, 6, 6.5, 7, 8 or 9.
[0028] 14. The method of any one of embodiments 9 to 13, wherein the reaction is carried out at temperatures between -10°C and 60°C, or between 5°C and 30°C, such as 25°C, 40°C, or at room temperature.
[0029] 15. The method of any one of embodiments 9 to 14, wherein the reaction is carried out for 5 to 60 hours, alternatively 10 to 48 hours, such as 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours or 45 hours.
[0030] 16. The method according to any one of embodiments 9 to 15, wherein after the reaction is completed, the pH is adjusted to the isoelectric point of oxidized glutathione (pH 2.75 to 2.90) and crystallization by stirring is carried out for at least 5 hours, alternatively at least 10 hours.
[0031] 17. The method of embodiment 16, wherein the crystallization by stirring is carried out at 5° C. to 40° C., alternatively at 5° C., 10° C., 15° C., 20° C. or at room temperature.
[0032] 18. The method according to any one of embodiments 9 to 17, wherein the purity of the compound of formula (I) obtained is ≧98%, alternatively ≧98.5%, alternatively ≧99%, alternatively ≧99.7%, alternatively ≧99.8%, alternatively ≧99.9%, and the total content of impurities A, B and C in the product is less than 1%, alternatively less than 0.5%, alternatively less than 0.3%, alternatively less than 0.1%.
[0033] [Table 2]
[0034] 19.1) dissolving crude oxidized glutathione in purified water, the amount of purified water being 3 to 5 times the weight of the crude oxidized glutathione; 2) After dissolution, hot filtering the solution; and 3) cooling the filtrate to 10-25°C, or 12-20°C for crystallization; A method for purifying oxidized glutathione according to any one of embodiments 9 to 18.
[0035] 20. The method of embodiment 19, wherein in step 1), the temperature of the purified water is 35°C to 55°C, or 40°C to 50°C, and optionally, an iron(II) chloride solution is added to remove residual raw materials, or 100 mL of a 5% iron(II) chloride solution is added per kilogram of oxidized glutathione.
[0036] 21. The method according to embodiment 19 or 20, wherein in step 3), the crystallization time of the recrystallization is 3-10 hours, alternatively 4-6 hours, and optionally employs gradient cooling, with a cooling rate of 10° C. per hour.
[0037] 22. Recrystallizing the oxidized glutathione prepared according to any one of embodiments 9 to 21 in purified water, the method comprising the steps of: 1) dissolving the oxidized glutathione in purified water and stirring until dissolved; 2) After dissolution, the solution is hot filtered and then gradient cooled to the target temperature; and 3) Temperature-controlled crystallization step 9. A method for preparing a crystal of oxidized glutathione heptahydrate according to any one of embodiments 1 to 8, comprising:
[0038] 23. The method of embodiment 22, wherein in step 1), 2L to 6L, alternatively 3L to 6L, further alternatively 3L to 5L, further alternatively 4L of purified water is used per kilogram of oxidized glutathione.
[0039] 24. The method according to embodiment 22 or 23, wherein in step 1), the temperature of the purified water during the dissolution process is 40-60°C, alternatively 40-50°C, further alternatively 50°C.
[0040] 25. The method according to any one of embodiments 22 to 24, wherein in step 1), an iron(II) chloride solution is added to better remove residual raw materials, and optionally, 100 mL of a 5% iron(II) chloride solution is added per kilogram of oxidized glutathione.
[0041] 26. The method according to any one of embodiments 22 to 25, wherein in step 2), the cooling gradient is 5 to 25° C. / h, alternatively 5 to 20° C. / h, alternatively 5 to 15° C. / h, further alternatively 10° C. / h.
[0042] 27. The method of any one of embodiments 22 to 26, wherein in step 2) the target temperature is 5 to 25°C, alternatively 10 to 25°C, further alternatively 15 to 25°C.
[0043] 28. The method according to any one of embodiments 22 to 27, wherein in step 3), the temperature is controlled at 5 to 25°C, alternatively at 10 to 25°C, further alternatively at 15 to 25°C.
[0044] 29. The method of any one of embodiments 22 to 28, wherein in step 3), the crystallization time is 6 to 12 hours, alternatively 6 to 8 hours.
[0045] 30. [Table 3] A compound selected from:
[0046] 31. [ka] comprising oxidizing reduced glutathione and Cys-Gly in a 1:1 molar ratio with DMSO; A method for preparing impurity A according to embodiment 30.
[0047] 32. The method of embodiment 31, wherein the amount of DMSO is from 2 to 10 equivalents, alternatively from 3 to 5 equivalents.
[0048] 33.1) Boc-Cys(Trt)-OH and glycine tert-butyl ester in a molar ratio of 1:1 to 1:3 are reacted with 1.5 to 4 equivalents of a condensing agent (e.g., HATU, HBTU, PyBOP, DEPBT, etc., or HBTU and DEPBT) and 2 equivalents of a tertiary organic amine (e.g., N,N-diisopropylethylamine and triethylamine, or N,N-diisopropylethylamine), which reaction is carried out in DMF or dichloromethane; 2) removal of the Trt, Boc and tBu protecting groups with trifluoroacetic acid to give Cys-Gly; and 3) oxidizing reduced glutathione and Cys-Gly in a 1:1 molar ratio with 3 to 5 equivalents of DMSO; The method of embodiment 31 or 32.
[0049] 34. [ka] oxidizing reduced glutathione and Glu-Cys in a 1:1 molar ratio with DMSO; A method for preparing impurity B according to embodiment 30.
[0050] 35. The method of embodiment 34, wherein the amount of DMSO is from 2 to 10 equivalents, alternatively from 3 to 5 equivalents.
[0051] 36.1) 1:1-1:2 molar ratio of Boc-Glu-OtBu and H-Cys(Trt)-OtBu is condensed under the catalytic action of 1.5-4 equivalents of a condensing agent (e.g., HATU, HBTU, PyBOP, DEPBT, etc., or HBTU and DEPBT) and 2 equivalents of a tertiary organic amine (e.g., N,N-diisopropylethylamine and triethylamine, or N,N-diisopropylethylamine); 2) removal of the Boc, Trt, and tBu protecting groups with trifluoroacetic acid to give Glu-Cys; and 3) oxidizing reduced glutathione and Glu-Cys in a 1:1 molar ratio with 3 to 5 equivalents of DMSO; The method according to embodiment 34 or 35.
[0052] 37. Oxidizing reduced glutathione and cysteine in a molar ratio of 1:1 with DMSO, A method for preparing impurity C as defined in embodiment 30.
[0053] 38. The method of embodiment 37, wherein the amount of DMSO is from 2 to 10 equivalents, alternatively from 3 to 5 equivalents.
[0054] Advantageous Effects of the Present Disclosure
[0055] The crude oxidized glutathione obtained by this method does not contain peroxidation impurities, has a relatively low content of hydrolysis impurities, and does not produce other solid by-products, which provides the basis and guarantee for subsequent quality control of oxidized glutathione after the structures of other impurities are analyzed and synthesized.
[0056] The present inventors used a small amount of aqueous iron(II) chloride solution during the purification process of oxidized glutathione. It was accidentally discovered that the addition of oxidized glutathione heptahydrate could unexpectedly significantly improve the purification effect and increase the purity of the product by recrystallization in purified water under specific conditions. [Brief description of the drawings]
[0057] [Figure 1] FIG. 1 is an ESI-MS profile of oxidized glutathione. [Diagram 2] FIG. 2 is an ESI-MS profile of impurity A of oxidized glutathione. [Diagram 3] FIG. 3 is an ESI-MS trace of impurity B of oxidized glutathione. [Figure 4] FIG. 4 is an ESI-MS profile of impurity C of oxidized glutathione. [Diagram 5] FIG. 5 is an X-ray powder diffraction pattern of a crystal of oxidized glutathione heptahydrate. [Figure 6] FIG. 6 shows TG and DSC diagrams of crystalline oxidized glutathione heptahydrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0058] definition
[0059] "Polar solvent" refers to a solvent that contains polar groups such as hydroxyl, carbonyl, carboxyl, etc., i.e., the solvent molecule is polar because the centers of gravity of the positive and negative charges in the molecule do not coincide, which makes the molecule polar. The polar solvent is selected from the group consisting of water, formamide, trifluoroacetic acid, acetonitrile, DMF, hexamethylphosphoramide, methanol, ethanol, acetic acid, isopropanol, pyridine, tetramethylethylenediamine, acetone, triethylamine, n-butanol, dioxane, tetrahydrofuran, methyl formate, tributylamine, methyl ethyl ketone, ethyl acetate, chloroform, trioctylamine, dimethyl carbonate, and diethyl ether, or combinations thereof.
[0060] "Isoelectric point" is the pH value at which a molecule loses its surface charge. At the isoelectric point, because there is no mutual repulsion due to identical charges, the molecule is most unstable, has the lowest solubility, and may rapidly combine into large aggregates due to electrostatic attraction, thereby precipitating.
[0061] The moisture content is calculated as follows:
[0062] Water content = mass of water molecules * number of water molecules in a single crystal molecule / (mass of water molecules * number of water molecules in a single crystal molecule + molecular weight of oxidized glutathione) * 100%
[0063] For example, the water content of the monohydrate = 18.01*1 / (18.01*1+612.63)*100% = 2.86%, the water content of the hexahydrate = 18.01*6 / (18.01*6+612.63) = 14.99%, the water content of the heptahydrate = 18.01*7 / (18.01*7+612.63) = 17.07%, and the water content of the octahydrate = 18.01*8 / (18.01*8+612.63) = 19.04%.
[0064] The embodiments of the present disclosure are described below clearly and completely with reference to the examples. Obviously, the described examples are only used to illustrate the present disclosure, but are not used to limit the present disclosure. Based on the examples of the present disclosure, all other examples obtained by those skilled in the art without creative efforts are included in the scope of protection of the present disclosure. EXAMPLES
[0065] (1) Synthesis of oxidized glutathione
[0066] Example 1
[0067] 1.0 kg of reduced glutathione and 10.0 L of water were added to a three-neck flask, and then 1.0 L of dimethyl sulfoxide was added to the three-neck flask. The mixture was reacted at room temperature for 48 hours with stirring. The solid was allowed to precipitate, and the solid was filtered and dried to obtain 950.2 g of crude oxidized glutathione, with a yield of 95.3% and a purity of 98.4%. ESI-MS [M+H] + =613.3.
[0068] Example 2
[0069] 1.0 kg of reduced glutathione and 3.0 L of water were added to a three-neck flask. The pH of the mixture was adjusted to 6-7 with NaOH, and then 500 mL of dimethyl sulfoxide was added. The mixture was stirred at room temperature for 10 h. The pH was adjusted to the isoelectric point (2.75-2.90), and the mixture was stirred at 5°C for 10 h for crystallization. The mixture was filtered. The filter cake was rinsed with ethanol and dried to obtain 855.1 g of crude oxidized glutathione, with a yield of 86.0% and a purity of 99.3%. ESI-MS [M+H] + =613.3.
[0070] Example 3
[0071] 1.0 kg of reduced glutathione and 2.5 L of water were added to a three-neck flask. The pH was adjusted to 6.0 with NaOH, and then 450 mL of dimethyl sulfoxide was added to the three-neck flask. The mixture was stirred at 40°C for 24 hours. The pH was adjusted to the isoelectric point (2.75-2.90), and the mixture was crystallized at 8°C for 10 hours. The mixture was filtered. The filter cake was rinsed with ethanol and dried to obtain 892.7 g of oxidized glutathione, with a yield of 89.5% and a purity of 99.0%. ESI-MS [M+H] + =613.3.
[0072] Example 4
[0073] 1.0 kg of reduced glutathione and 3.0 L of water were added to a three-neck flask. The pH was adjusted to 5.5 with NaOH, and then 550 mL of dimethyl sulfoxide was added to the three-neck flask. The mixture was stirred at 25°C for 48 hours. The pH was adjusted to the isoelectric point (2.75-2.90), and the mixture was crystallized at 5°C for 8 hours. The mixture was filtered. The filter cake was rinsed with ethanol and dried to obtain 912.0 g of oxidized glutathione, with a yield of 91.5% and a purity of 99.2%. ESI-MS [M+H] + =613.3.
[0074] Comparative Example 1: Oxidation with Hydrogen Peroxide
[0075] 10g reduced glutathione and 30mL water were added into a three-neck flask. The pH was adjusted to 5.8 with NaOH, and 3.3mL 30% hydrogen peroxide was added into the three-neck flask at room temperature in a water bath. The mixture was reacted for 5 hours. Then the pH was adjusted to 3.0, and 50mL absolute ethanol was added into the system. The mixture was crystallized at 10°C for 10 hours, and then filtered. The filter cake was rinsed with ethanol and dried to obtain 9.09g oxidized glutathione containing peroxide impurities, with a yield of 91.2% and a purity of 96.2%. ESI-MS [M+H] + =613.3.
[0076] (2) Purification of oxidized glutathione
[0077] Comparative Example 2: Purification and refining by conventional methods
[0078] 10 g of crude oxidized glutathione obtained in the above (1) Synthesis of oxidized glutathione The glutathione was dissolved in 200 mL of purified water. The sample was then injected into a strong acid cation exchange resin and eluted with purified water. The eluate was collected and the solid was then precipitated by adding absolute ethanol to obtain 8.43 g of oxidized glutathione, with a one-step yield of 84.3% and a purity of 99.5%. The increase in purity was 0.2%.
[0079] Example 5 1.0 kg of crude oxidized glutathione obtained in the above (1) Example of synthesis of oxidized glutathione was added to 4.0 L of purified water at 50°C, and 100 mL of 5% iron (II) chloride solution was added. The mixture was stirred until the solid was dissolved. The mixture was filtered while hot, and then gradually cooled to 25°C at 10°C per hour. Finally, the mixture was controlled at a temperature of 20°C to 25°C and crystallized for 8 hours. The mixture was filtered. The filter cake was rinsed with ethanol and dried.
[0080] In another example experiment, the steps above were carried out in sequence using the parameters in the table below.
[0081] Searching for settling time
[0082] [Table 4]
[0083] [Table 5]
[0084] According to the above results, if the crystallization time is too short, the obtained crystals are a mixture of crystals with unstable water content, and if the crystallization time is too long, impurities will precipitate and the purity of the product will decrease. Therefore, the crystallization time is alternatively 6-12 hours, or alternatively 6-8 hours.
[0085] Searching for twice the amount of purified water
[0086] [Table 6]
[0087] [Table 7]
[0088] According to the above results, when purified water is used to dissolve oxidized glutathione, the amount of water has a great effect on the yield. If the amount of water is too much, the yield will be very low. If the amount of water is too little, the product cannot be completely dissolved, or after dissolution and reprecipitation, the stirring effect is not very effective, and the product purity will decrease. Therefore, the amount of water is alternatively 2-6 times, alternatively 3-6 times, and even alternatively 3-5 times.
[0089] Searching for melting temperature
[0090] [Table 8]
[0091] [Table 9]
[0092] According to the above table: when the temperature is higher than 40°C, all the examples are soluble, but when the temperature is higher than 60°C, the racemization phenomenon occurs. Moreover, the higher the temperature, the longer the heating time, and the more serious the racemization phenomenon becomes. Considering the energy consumption of the product, the selected temperature is 40-60°C, or 40-50°C, or even 50°C.
[0093] Search for crystallization temperature
[0094] [Table 10]
[0095] [Table 11]
[0096] According to the above experimental results, if the crystallization temperature is too low, the yield is high, but many impurities are also precipitated, and the content of a single impurity exceeds 0.1%. If the crystallization temperature is too high, the yield will gradually decrease. Comprehensively considering the above factors, the selected crystallization temperature may be 5-25°C, or 10-25°C, or even 15-25°C.
[0097] Exploring cooling gradients
[0098] [Table 12]
[0099] [Table 13]
[0100] According to the above table, if the cooling rate is too fast, the crystallization rate is fast, but impurities are included and precipitate quickly, and the purity of the product is reduced. If the cooling rate is too slow, the crystallization time is long, energy consumption and labor costs increase, while the yield does not change much. Therefore, considering all factors, the cooling rate can be 5-20°C / h, or 5-15°C / h, or even 10°C / h.
[0101] Example 25 1.0 kg of crude oxidized glutathione obtained in the above (1) Example of the synthesis of oxidized glutathione was added to 4.0 L of purified water at 40°C, and the mixture was stirred until the solid was dissolved. The mixture was filtered while hot, and then gradually cooled to 20°C at 10°C per hour. Finally, the mixture was controlled at a temperature of 15°C to 20°C and crystallized for 8 hours. The mixture was filtered. The filter cake was rinsed with ethanol and dried to obtain 855.1 g of oxidized glutathione, with a one-step yield of 85.5% and a purity of 99.7%. The increase in purity was 0.5%.
[0102] Example 26
[0103] 1.0 kg of crude oxidized glutathione obtained in the above (1) Example of the synthesis of oxidized glutathione was added to 4.0 L of purified water at 45 ° C, and 100 mL of 5% iron (II) chloride solution was added. The mixture was stirred until the solid was dissolved. The mixture was filtered while hot, and then gradually cooled to 20 ° C at 10 ° C per hour. Finally, the mixture was controlled at a temperature of 15 ° C to 20 ° C and crystallized for 7 hours. The mixture was filtered. The filter cake was rinsed with ethanol and dried to obtain 849.2 g of oxidized glutathione, with a one-step yield of 84.9% and a purity of 99.9%. The increase in purity was 0.7%.
[0104] Example 27
[0105] 1.0 kg of crude oxidized glutathione obtained in the above (1) Example of synthesis of oxidized glutathione Glutathione was added to 5.0 L of purified water at 50°C, and the mixture was stirred until the solid was dissolved. The mixture was hot filtered, and then gradually cooled to 20°C at 10°C per hour. Finally, the mixture was controlled at a temperature of 15°C to 20°C and crystallized for 8 hours. The mixture was filtered. The filter cake was rinsed with ethanol and dried to obtain 843.3 g of oxidized glutathione, with a one-step yield of 84.3% and a purity of 99.7%. The increase in purity was 0.5%.
[0106] Example 28
[0107] 1.0 kg of crude oxidized glutathione obtained in the above (1) Example of the synthesis of oxidized glutathione was added to 5.0 L of purified water at 50 ° C, and 100 mL of 5% iron (II) chloride solution was added. The mixture was stirred until the solid was dissolved. The mixture was filtered while hot, and then gradually cooled to 20 ° C at 10 ° C per hour. Finally, the mixture was controlled at a temperature of 15 ° C to 20 ° C and crystallized for 8 hours. The mixture was filtered. The filter cake was rinsed with ethanol and dried to obtain 848.6 g of oxidized glutathione, with a one-step yield of 84.9% and a purity of 99.9%. The increase in purity was 0.7%.
[0108] Example 29
[0109] 1.0 kg of crude oxidized glutathione obtained in the above (1) Example of the synthesis of oxidized glutathione was added to 4.0 L of purified water at 50°C, and the mixture was stirred until the solid was dissolved. The mixture was filtered while hot, and then gradually cooled to 20°C at 10°C per hour. Finally, the mixture was controlled at a temperature of 20°C to 25°C and crystallized for 6 hours. The mixture was filtered. The filter cake was rinsed with ethanol and dried to obtain 851.6 g of oxidized glutathione, with a one-step yield of 85.2% and a purity of 99.7%. The increase in purity was 0.5%.
[0110] Example 30
[0111] Preparation of Impurity A: 4.6g Boc-Cys(Trt)-OH, 1.7g glycine tert-butyl hydrochloride and 7.6g HBTU were dissolved in 30mL DMF, and 2mL DIEA was added dropwise to the mixture. The reaction was carried out at room temperature for 24 hours, and then 100mL water was added. The mixture was extracted with ethyl acetate three times, and the organic phase was kept and dried over anhydrous magnesium sulfate. The solvent was evaporated to dryness, and then the residue was dissolved in 30mL dichloromethane. 30mL of 30% aqueous trifluoroacetic acid was added to remove protective groups such as Trt, Boc and tBu. After the reaction was completed, the layers were separated and the aqueous layer was kept. Then 50mL of ethanol was added to the aqueous layer to precipitate the solid. The mixture was suction filtered, and the filter cake was purified by preparative liquid phase chromatography to obtain Cys-Gly. Then reduced glutathione and Cys-Gly in a 1:1 molar ratio were dissolved in 20mL water. For oxidation, 5 equivalents of DMSO were added to the mixture. The reaction was carried out at room temperature for 10 hours, and then 40 mL of ethanol was added to precipitate the solid. The resulting solid was dissolved in 5 mL of 1% aqueous trifluoroacetic acid, and the mixture was separated by preparative liquid phase chromatography. The mobile phases were Phase A: 1% trifluoroacetic acid / water; and Phase B: 1% trifluoroacetic acid / acetonitrile. Finally, 2.0 g of impurity A was obtained by lyophilization, with a total yield of 42% and a purity of 99.7%. ESI-MS [M+H] + =484.1.
[0112] Example 31
[0113] Preparation of impurity B: Dissolve 3.0 g of Boc-Glu-OtBu, 4.2 g of HCl H-Cys(Trt)-OtBu, and 7.6 g of HBTU in 30 mL of DMF and add 3 mL of DIEA was added dropwise to the mixture. The reaction was carried out at room temperature for 18 hours, then 100 mL of water was added. The mixture was extracted with ethyl acetate three times, and the organic phase was retained and dried over anhydrous magnesium sulfate. The solvent was evaporated to dryness, and then the residue was dissolved in 30 mL of dichloromethane. To remove protective groups such as Trt, Boc, and tBu, 40 mL of 30% aqueous trifluoroacetic acid was added. After the reaction was completed, the aqueous layer was separated. Then 50 mL of ethanol was added to the aqueous layer to precipitate the solid. The mixture was suction filtered, and the filter cake was purified by preparative liquid-phase chromatography to obtain Glu-Cys. Then reduced glutathione and Glu-Cys in a 1:1 molar ratio were dissolved in 20 mL of water. For oxidation, 5 equivalents of DMSO were added to the mixture. The reaction was carried out at room temperature for 12 hours, and then 40 mL of ethanol was added to precipitate the solid. The resulting solid was dissolved in 5 mL of purified water, and the mixture was separated by preparative liquid-phase chromatography. The mobile phase was Phase A: 1% trifluoroacetic acid / water; and Phase B: 1% trifluoroacetic acid / acetonitrile. Finally, 2.3 g of impurity B was obtained by lyophilization, with an overall yield of 41% and a purity of 99.7%. ESI-MS [M+H] + =555.2.
[0114] Example 32
[0115] Preparation of impurity C: 3.1g reduced glutathione and 1.2g cysteine were added to 15mL water, and 3.9g DMSO was added for oxidation. The mixture was reacted under stirring at room temperature for 9 hours. After the reaction was completed, 30mL ethanol was added to precipitate the solid. The resulting solid was dissolved in 5mL purified water, and the mixture was separated by preparative liquid phase chromatography. The mobile phases were phase A: 1% trifluoroacetic acid / water; and phase B: 1% trifluoroacetic acid / acetonitrile. Finally, 2.1g impurity C was obtained by lyophilization, with a total yield of 49% and a purity of 99.8%. ESI-MS [M+H] + =427.1.
[0116] (3) Crystal characteristics and analysis
[0117] After the test, the melting point of the obtained crystal was 169°C (microscope melting point measuring apparatus X-5, manufacturer: Corey Instrument), which was different from the melting point of the reported crystal, proving that this crystal was a new crystal form; and the characteristic peaks (3 high peaks and 8 high peaks) obtained by X-ray powder diffraction test (specification: D8 ADVANCE, manufacturer: Bruker Company, Germany, equipped with LynxEye detector, 2θ scanning angle 3°-40°, scanning step size 0.02°, scanning speed 0.3 sec / step, and tube voltage and tube current during sample measurement are 40 KV and 40 mA, respectively) also did not match with the reported crystal form, and at the same time, the relevant peak shapes proved that the crystal form was not a mixture of crystals; and the TG-DSC test (specification model: STA 449F5, manufacturer: NETZSCH, After heating at 37 °C (Germany), the weight loss of the sample from 50 to 180 °C was measured at a slow heating rate (1.0 °C / min), and the water content of the obtained oxidized glutathione was 17.2%, which was essentially consistent with the water content of the sample measured by a Karl Fischer moisture meter (model: V20S, manufacturer: METTLER TOLEDO) (17.2%, the result of three parallel runs). Since the water content was consistent with the water content of oxidized glutathione heptahydrate calculated above, the obtained crystal was determined to be oxidized glutathione heptahydrate.
[0118] Table 11 below shows the difference in saturation solubility between the above-mentioned crystalline oxidized glutathione heptahydrate and the crystalline oxidized glutathione monohydrate and hexahydrate.
[0119] [Table 14]
[0120] At the same temperature, the water solubility of the heptahydrate is significantly better than that of the monohydrate and comparable to that of the hexahydrate. Moreover, compared to the powder crystals of the hexahydrate, which tend to generate static electricity and suffer large losses during the packaging process, the obtained granular crystals of the heptahydrate are more suitable for industrial production.
[0121] [Table 15]
[0122] In summary, the present disclosure provides a method for preparing oxidized glutathione and new crystalline forms thereof, as well as impurities. The present invention provides a method for synthesizing oxidized glutathione, thereby simplifying the synthesis method of oxidized glutathione. The synthesis of impurities provides a guarantee for the subsequent quality test of oxidized glutathione. At the same time, using purified water to recrystallize the synthesized oxidized glutathione not only obtains high-purity oxidized glutathione, but also simplifies the existing purification method. Compared with the existing crystal forms, the newly discovered new crystal form of heptahydrate has a simpler synthesis method, good water solubility, good stability, and is more suitable for the industrial production of oxidized glutathione.
Claims
1. Formula (I): 【Chemistry 1】 A crystal of the heptahydrate of the compound.
2. 2. The crystal of claim 1, characterized by an X-ray powder diffraction pattern obtained using CuKα radiation having at least the following characteristic peaks at °2θ: 8.238±0.2, 16.338±0.2, and 24.551±0.
2.
3. 3. The crystal of claim 2, characterized by an X-ray powder diffraction pattern obtained using CuKα radiation having at least the following characteristic peaks at °2θ: 10.619±0.2, 19.539±0.2, 26.806±0.2, and 34.618±0.
2.
4. 4. The crystal of claim 3, characterized by an X-ray powder diffraction pattern obtained using CuKα radiation having at least the following characteristic peaks at °2θ: 9.750±0.2, 22.738±0.2, and 23.200±0.
2.
5. 2. The crystal of claim 1, characterized by an X-ray powder diffraction pattern substantially as shown in FIG.
6. The crystal of any one of claims 1 to 5, further characterized by having a melting point of 169±2°C.
7. 7. The crystal of any one of claims 1 to 6, further characterized by a weight loss of about 14±1% at 50-100°C and a weight loss of about 3±1% at 100-160°C in thermogravimetric analysis.
8. The crystal of any one of claims 1 to 7, further characterized in that it has a thermogravimetric diagram as shown in Figure 6.
9. Formula (II) 【Chemistry 2】 with DMSO to obtain a compound of formula (I), A process for preparing a compound of formula (I).
10. 10. The method of claim 9, wherein the molar ratio of DMSO to the compound of formula (II) is from 2:1 to 25:1, alternatively from 2.5:1 to 5:1, further alternatively 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:
1.
11. 11. The method of claim 9 or 10, wherein a polar solvent is further added to the reaction to facilitate dissolution of the compound of formula (II), optionally the polar solvent is selected from the group consisting of water, formamide, trifluoroacetic acid, acetonitrile, DMF, hexamethylphosphoramide, methanol, ethanol, acetic acid, isopropanol, pyridine, tetramethylethylenediamine, acetone, triethylamine, n-butanol, dioxane, tetrahydrofuran, methyl formate, tributylamine, methyl ethyl ketone, ethyl acetate, chloroform, trioctylamine, dimethyl carbonate and diethyl ether, or combinations thereof, and further alternatively water.
12. 12. The method of claim 11, wherein the ratio of polar solvent to compound of formula (II) is from 200 to 2000 mL, alternatively from 250 mL to 1000 mL, further alternatively 250 mL, 300 mL, 500 mL, 750 mL or 1000 mL of polar solvent per 100 g of compound of formula (II).
13. 13. A method according to any one of claims 9 to 12, wherein the pH of the reaction is adjusted to from 2 to 9, alternatively from 3 to 7, further alternatively to 5 to 7, such as 5, 5.5, 6, 6.5, 7, 8 or 9.
14. 14. The method of any one of claims 9 to 13, wherein the reaction is carried out at a temperature between -10°C and 60°C, or between 5°C and 30°C, such as 25°C, 40°C or at room temperature.
15. 15. The method of any one of claims 9 to 14, wherein the reaction is carried out for a period of from 5 to 60 hours, alternatively from 10 to 48 hours, such as 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours or 45 hours.
16. 16. The method of any one of claims 9 to 15, wherein after the reaction is completed, the pH is adjusted to the isoelectric point of oxidized glutathione (pH 2.75-2.90) and crystallization by stirring is carried out for at least 5 hours, alternatively for at least 10 hours.
17. The crystallization by stirring is carried out at 5°C to 40°C, or at 5°C, 10°C, 15°C, 20°C or room temperature. The method of claim 16 carried out at room temperature.
18. 18. The process according to any one of claims 9 to 17, wherein the purity of the compound of formula (I) obtained is ≧98%, alternatively ≧98.5%, alternatively ≧99%, alternatively ≧99.7%, alternatively ≧99.8%, alternatively ≧99.9%, and the total content of impurities A, B and C in the product is less than 1%, alternatively less than 0.5%, alternatively less than 0.3%, alternatively less than 0.1%. 【Table 1】
19. 1) dissolving crude oxidized glutathione in purified water, the amount of the purified water being 3 to 5 times the weight of the crude oxidized glutathione; 2) hot filtering the solution after dissolution; and 3) cooling the filtrate to 10-25°C, alternatively 12-20°C, for crystallization; A method for purifying oxidized glutathione according to any one of claims 9 to 18.
20. 20. The method of claim 19, wherein in step 1), the temperature of the purified water is between 35°C and 55°C, alternatively between 40°C and 50°C, and optionally adding iron (II) chloride solution to remove residual raw materials, or adding 100 mL of 5% iron (II) chloride solution per kilogram of oxidized glutathione.
21. The method according to claim 19 or 20, wherein in step 3), the crystallization time of the recrystallization is 3-10 hours, alternatively 4-6 hours, and optionally employing gradient cooling, the cooling rate is 10° C. per hour.
22. 22. The method according to claim 9, further comprising the step of recrystallizing the oxidized glutathione prepared according to claim 9 in purified water, optionally comprising the steps of: 1) dissolving the oxidized glutathione in purified water and stirring until dissolved; 2) after said dissolution, hot filtering said solution and then gradient cooling to a target temperature; and 3) Crystallization under temperature control 9. A method for preparing a crystal of oxidized glutathione heptahydrate according to any one of claims 1 to 8, comprising:
23. 23. The method of claim 22, wherein in step 1), 2L to 6L, alternatively 3L to 6L, further alternatively 3L to 5L, further alternatively 4L of purified water is used per kilogram of oxidized glutathione.
24. The method according to claim 22 or 23, wherein in step 1), the temperature of the purified water during the dissolution process is 40-60°C, alternatively 40-50°C, further alternatively 50°C.
25. 25. The method according to any one of claims 22 to 24, wherein in step 1) iron(II) chloride solution is added to better remove residual raw materials, and optionally 100 mL of 5% iron(II) chloride solution is added per kilogram of oxidized glutathione.
26. 26. The method of any one of claims 22 to 25, wherein in step 2) the cooling gradient is from 5 to 25°C / hr, alternatively from 5 to 20°C / hr, alternatively from 5 to 15°C / hr, further alternatively 10°C / hr.
27. 27. The method of any one of claims 22 to 26, wherein in step 2) the target temperature is from 5 to 25°C, alternatively from 10 to 25°C, further alternatively from 15 to 25°C.
28. 28. The method of any one of claims 22 to 27, wherein in step 3) the temperature is controlled at 5 to 25°C, alternatively at 10 to 25°C, further alternatively at 15 to 25°C.
29. The method according to any one of claims 22 to 28, wherein in step 3), the crystallization time is from 6 to 12 hours, alternatively from 6 to 8 hours.
30. 【Table 2】 A compound selected from:
31. 【Chemical 3】 comprising oxidizing a 1:1 molar ratio of reduced glutathione and Cys-Gly with DMSO; 31. A method for preparing impurity A according to claim 30.
32. 32. The method of claim 31 , wherein the amount of DMSO is from 2 to 10 equivalents, alternatively from 3 to 5 equivalents.
33. 1) condensation of Boc-Cys(Trt)-OH and glycine tert-butyl ester in a molar ratio of 1:1 to 1:3 under the catalysis of 1.5 to 4 equivalents of a condensing agent (e.g., HATU, HBTU, PyBOP, DEPBT, etc., or HBTU and DEPBT) and 2 equivalents of a tertiary organic amine (e.g., N,N-diisopropylethylamine and triethylamine, or N,N-diisopropylethylamine), wherein the reaction is carried out in the presence of DMF. or in dichloromethane, 2) removal of the Trt, Boc and tBu protecting groups with trifluoroacetic acid to give Cys-Gly; and 3) oxidizing a 1:1 molar ratio of reduced glutathione and Cys-Gly with 3-5 equivalents of DMSO; 33. The method of claim 31 or 32.
34. 【Chemical 4】 comprising oxidizing reduced glutathione and Glu-Cys in a 1:1 molar ratio with DMSO; 31. A method for preparing impurity B according to claim 30.
35. 35. The method of claim 34, wherein the amount of DMSO is from 2 to 10 equivalents, alternatively from 3 to 5 equivalents.
36. 1) condensation of Boc-Glu-OtBu and H-Cys(Trt)-OtBu in a molar ratio of 1:1 to 1:2 under the catalysis of 1.5 to 4 equivalents of a condensing agent (e.g., HATU, HBTU, PyBOP, DEPBT, etc., or HBTU and DEPBT) and 2 equivalents of a tertiary organic amine (e.g., N,N-diisopropylethylamine and triethylamine, or N,N-diisopropylethylamine); 2) removal of the Boc, Trt, and tBu protecting groups with trifluoroacetic acid to give Glu-Cys; and 3) oxidizing reduced glutathione and Glu-Cys in a 1:1 molar ratio with 3-5 equivalents of DMSO; 36. The method of claim 34 or 35.
37. oxidizing reduced glutathione and cysteine in a 1:1 molar ratio with DMSO; 31. A method for preparing impurity C according to claim 30.
38. 38. The method of claim 37, wherein the amount of DMSO is from 2 to 10 equivalents, alternatively from 3 to 5 equivalents.